2012
DOI: 10.1002/hipo.22065
|View full text |Cite
|
Sign up to set email alerts
|

The perirhinal cortex modulates V2 activity in response to the agreement between part familiarity and configuration familiarity

Abstract: ABSTRACT:Research has demonstrated that the perirhinal cortex (PRC) represents complex object-level feature configurations, and participates in familiarity versus novelty discrimination. Barense et al. [(in press) Cerebral Cortex, 22:11, doi:10.1093/cercor/bhr347] postulated that, in addition, the PRC modulates part familiarity responses in lower-level visual areas. We used fMRI to measure activation in the PRC and V2 in response to silhouettes presented peripherally while participants maintained central fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
60
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 80 publications
17
60
0
Order By: Relevance
“…Healthy controls, who presumably had an intact PRC, performed as well under conditions of High Interference as they did under conditions of Low Interference; it was only the PRC-damaged group who were susceptible to the high levels of visual interference. These findings provide evidence to support the idea that the PRC is critical for representing the complex conjunctions of features that distinguish perceptually similar objects (see also Baxter, 2012;Peterson et al, 2012;Ryan et al, 2012). These PRC representations become essential when repeated presentation of multiple, similar features causes interference at the level of the features represented by intact posterior regions in the ventral visual stream.…”
Section: Introductionsupporting
confidence: 71%
“…Healthy controls, who presumably had an intact PRC, performed as well under conditions of High Interference as they did under conditions of Low Interference; it was only the PRC-damaged group who were susceptible to the high levels of visual interference. These findings provide evidence to support the idea that the PRC is critical for representing the complex conjunctions of features that distinguish perceptually similar objects (see also Baxter, 2012;Peterson et al, 2012;Ryan et al, 2012). These PRC representations become essential when repeated presentation of multiple, similar features causes interference at the level of the features represented by intact posterior regions in the ventral visual stream.…”
Section: Introductionsupporting
confidence: 71%
“…Cues that bring "good" news automatically enhance visual responses and attract attention toward their location, whereas cues that bring "bad" news automatically inhibit visual responses and repel attention away from their location (Peck et al, 2009). In other words, the brain seems to modify its processing of sources of information according to the "message" it receives even when there is no opportunity for an active choice.…”
Section: Discussionmentioning
confidence: 99%
“…When the cues appeared in their RF (Fig. 4, top row), LIP neurons had visual transient and sustained postcue responses that were stronger for positive relative to negative cues (see below and Peck et al, 2009). In addition, responses were stronger for novel relative to familiar patterns.…”
Section: Lip Neurons Show Converging But Distinct Effects Of Novelty mentioning
confidence: 95%
“…Thus, we expected to observe evidence of competition-mediated ground suppression in the LH when we presented our silhouettes in the RVF, but we were uncertain whether we would observe evidence of competition-mediated ground suppression in the right hemisphere (RH) when we presented our silhouettes in the LVF, especially given that our stimuli are so different from those previously used. Moreover, prior studies have observed different patterns of activation in the LH and RH visual cortex when participants made familiarity judgments regarding figure-ground stimuli (Peterson, Cacciamani, Barense, & Scalf, 2012), suggesting that neural responses are not consistent across hemispheres. Accordingly, we plan to test activation in each hemisphere separately.…”
Section: !mentioning
confidence: 93%